The Effect of Return on Asset (RoA), Earning Management and Audit Committee on Audit Delay with Managerial Ownership as a Moderating Variable - Sadewo, Dian; Saputra, Dian (International Journal of Science and Society, 2024)
This study looks into the effects of return on asset (RoA), earnings management, and the audit committee on audit delay, with managerial ownership acting as a moderating variable. Committee of AuditsBetween 2020 and 2022, this study was carried out at property and real estate companies that were listed on Indonesia's stock exchange. Audited financial accounts serve as the source of secondary data that is used. Partial Least Square Structural Equation Modeling (SEM-PLS) is the data analysis method used. The findings demonstrated that, although profitability and earning management had a major impact on audit delay, the Committee on Audit had no discernible impact and was bolstered by managerial ownership as a mitigating factor.